Effect of variable thermal conductivity and viscosity on Casson nanofluid flow with convective heating and velocity slip - J.A. Gbadeyan (Heliyon, 2020)
This work investigates the effects of combined variable viscosity and thermal conductivity, nonlinear radiation and non-Darcian porous medium on a boundary layer MHD Casson nanofluid flow over a vertical flat plate with convective heating and velocity slip boundary conditions. The governing transport nonlinear partial differential equations and the boundary conditions are non-dimensionalized. The resulting system of coupled partial differential equations is then reduced to a set of coupled nonlinear ordinary differential equations using similarity transformation. Galerkin weighted residual method (GWRM) is then employed to solve the resulting set of equations. Numerical results are obtained for dimensionless velocity, temperature and nanoparticle volume fraction (nanoparticle concentration). It is found that the velocity increases, while both temperature and nanoparticle volume fraction decrease with increased values of variable thermal conductivity and viscosity. Comparisons are carried out with published data in the literature thereby validating the numerical results. An excellent agreement is observed. Furthermore, this present study can find applications in the process involving nanofluid operations.